Examining the joint contribution of placental NR3C1 and HSD11B2 methylation for infant neurobehavior. (February 2015) - Appleton, Allison A.; Lester, Barry M.; Armstrong, David A.; Lesseur, Corina; Marsit, Carmen J.
Highlights: We examine placental epigenetic contributions of HPA genes for infant neurobehavior. NR3C1 and HSD11B2 methylation interact to predict different neurobehavior domains. Various methylation patterns across genes led to diverse neurobehavioral phenotypes. Summary: Infant neurobehavior, a potential sentinel of future mental and behavioral morbidity characterized in part by reflex symmetry, excitability and habituation to stimuli, is influenced by aspects of the intrauterine environment partially through epigenetic alterations of genes involved in the stress response. DNA methylation of two related cortisol response genes, the glucocorticoid receptor ( NR3C1 ), a nuclear receptor to which cortisol binds, and 11-beta hydroxysteroid dehydrogenase ( HSD11B2 ), the enzyme responsible for conversion of cortisol into inactive cortisone, independently associate with infant neurobehavior. Although these factors are part of a common cortisol regulation pathway, the combined effect of DNA methylation of these factors on infant neurobehavior has not been characterized. Therefore, we conducted an examination of the joint contribution of NR3C1 and HSD11B2 DNA methylation on infant neurobehavior. Among 372 healthy term newborns, we tested the interaction between placental NR3C1 and HSD11B2 DNA methylation in association with neurobehavior as assessed with the validated NICU Network Neurobehavioral Scales. Controlling for confounders, interactions between DNA methylation of these genes were detected for distinct domains of neurobehavior (habituation, excitability, asymmetrical reflexes). Moreover, different patterns of DNA methylation across the cortisol regulation pathway associated with different neurobehavioral phenotypes. Those with low NR3C1 methylation but high HSD11B2 methylation had lower excitability scores; those with high NR3C1 methylation but low HSD11B2 methylation had more asymmetrical reflexes; those with high DNA methylation across the entire pathway had higher habituation scores. These results suggest that epigenetic alterations across the cortisol regulation pathway may contribute to different neurobehavioral phenotypes, likely though varying degrees of glucocorticoid exposure during gestation. While the postnatal environment may continue to affect neurobehavioral risk, this study provides novel insights into the molecular basis for fetal origins of mental conditions.